Particle size-resolved source apportionment of primary and secondary organic tracer compounds at urban and rural locations in Spain - B. L. van Drooge; J. O. Grimalt (Atmospheric Chemistry and Physics, 2015)
Atmospheric particulate matter (PM) was fractionated in six aerodynamic sizes, > 7.2, 7.2–3, 3–1.5, 1.5–1, 1–0.5 and < 0.5 μm, using a cascade impactor. These fractions were collected at urban and rural sites during warm and cold seasons. Organic tracer compounds, such as levoglucosan, isoprene, pinene oxidation products, polycyclic aromatic hydrocarbons and quinones, were analyzed by gas chromatography coupled with mass spectrometry. These analyses showed that the composition in the smallest size fractions (< 0.5 μm) was more uniform than in the larger sizes (7.2> PM > 0.5 μm). Thus, markers of photochemically synthesized organic compounds or combustion sources, either biomass burning or traffic emissions, were predominantly observed in the fraction < 0.5 μm, whereas the larger particles were composed of mixed sources from combustion processes, vegetation emissions, soil resuspension, road dust, urban lifestyle activities and photochemically synthesized organic compounds. Important seasonal differences were observed at the rural site. In the < 0.5 μm fraction these were related to a strong predominance of biomass burning in the cold period and photochemically transformed biogenic organic compounds in the warm period. In the 7.2 > PM > 0.5 μm fractions the differences involved predominantly soil-sourced compounds in the warm period and mixed combustion sources, photochemical products and vegetation emissions in the cold.